Hubungan Berat Badan Lahir Rendah dan Penyakit Infeksi dengan Kejadian Stunting pada Baduta di Desa Maron Kidul Kecamatan Maron Kabupaten Probolinggo - Novianti Tysmala Dewi; Dhenok Widari (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2018)
Background: Stunting is a nutritional problem that has a high prevalence in Indonesia. Stunting among children under two years of age has a higher risk compared to other age groups because it will permanently affect the physical and cognitive development of children in the future. Factors that can cause stunting include low birth weight and infectious diseases.Objectives: The aim of this study was to determine the relationship between low birth weight and infection disease with incident of stunting among children under two years of age in Maron sub district, District of Probolinggo, East Java. Methods: This research was an observational research with case-control design. Sampling technique using multistage random sampling. the study was conducted in June until July 2018. The samples of study were 52 children (26 stunted children in case group and 26 normal growth children in control group. Data collection of infectious diseases was carried out by structured questionnaire interviews and medical records while low birth weight was obtained by looking at KIA book. Stunting was determined from measurement of children's recumbent length by metline. Data were analyzed by using chi square test for determining odds ratio. Results: The results showed that low birth weight (p=0.042; OR=0.157; 95% CI: 0.030-0.822) and infection disease (p=0.049; OR=3.071; 95% CI: 1.155-11.861) had significant relation with stunting among children under two years of age. Conclusions: Low birth weight and infection disease in the last 3 months increased the risk of 0.157 and 3.017 times stunting among children under two years of age. It is recommended for children under two years of age who have low birth weight and infectious disease should be given special attention by Integrated Health Post and there should be a monitoring related development routinely so developmental disruptions can be identified and immediately get the treatment. ABSTRAKLatar Belakang:Stunting merupakan masalah gizi yang memiliki prevalensi tinggi di Indonesia. Stunting pada baduta memiliki risiko lebih tinggi jika dibanding dengan kelompok usia lain karena akan berdampak secara permanen terhadap perkembangan fisik dan kognitif anak dimasa depan. Faktor penyebab stunting diantaranya adalah berat badan lahir rendah dan penyakit infeksi.Tujuan: Penelitian ini bertujuan untuk untuk menganalisis hubungan antara berat badan lahir rendah dan penyakit infeksi dengan kejadian stunting pada baduta di Desa Maron Kidul Kecamatan Maron, Kabupaten Probolinggo.Metode: Jenis penelitian menggunakan desain case-control. Sampel diambil dengan teknik sampel acak bertahap. Penelitian dilakukan pada bulan Juni hingga Juli 2018. Besar sampel sebanyak 52 baduta (26 anak stunting dan 26 anak non-stunting). Pengumpulan data penyakit infeksi dilakukan dengan wawancara kuisioner terstruktur dan rekam medik sedangkan berat badan lahir rendah diperoleh dengan melihat buku KIA. Penentuan stunting baduta diperoleh melalui pengukuran panjang badan dengan metline. Data dianalisis menggunakan chi-square untuk menentukan odds ratio.Hasil: Hasil penelitian menunjukkan ada hubungan berat badan lahir rendah (p=0.042; OR=0,157; 95% CI: 0,030-0,822), dan penyakit infeksi (p=0,049; OR=3,071; 95% CI: 1,155-11,861) dengan kejadian stunting pada baduta. Kesimpulan:Berat badan lahir rendah dan Rerat badan lahir rendah dan dutdah diperoleh dengan melihat buku KIA. of alcohol penyakit infeksi dalam 3 bulan terakhir meningkatkan risiko sebesar 0,157 dan 3,017 kali terhadap kejadian stunting pada baduta. Disarankan untuk baduta yang memiliki masalah BBLR dan penyakit infeksi diberikan perhatian khusus oleh posyandu serta perlu dilakukan peninjauan terkait perkembangan secara rutin agar gangguan perkembangan yang mungkin terjadi dapat segera dikenali dan diatasi.